ANTIBACTERIAL ACTIVITY OF MIXED MAULI BANANA STEM AND BASIL LEAVES AGAINST Staphylococcus aureus - Melisa Budipramana; Yunike Christanti; Maharani Laillyza Apriasari; Juliyatin Putri Utami (FKG Unlam, 2023)
ABSTRACTBackground: Mauli banana is a typical plant in South Kalimantan which contains tannins (67.59%), saponins (14.49%), alkaloids (0.34%), and flavonoids (0.25%) as natural antiseptics inhibiting the growth of Streptococcus mutans. Basil is plant that contain eugenol (70%), flavonoids (4.75%), tannins (4.6%), and alkaloids (1%) as natural antiseptics inhibiting the growth of Candida albicans. This study was to examine the antibacterial activity of a mixture of banana mauli stem stems and basil leaves against Staphylococcus aureus. Purpose: to analyze the antibacterial activity against Staphylococcus aureus in the mixture of banana mauli stems and basil leaves extracts. Method: true experiment using pretest and posttest with control group design with 11 treatments consisting of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, and aquadest. Antibacterial activity test was conducted using dilution method. Determination of Minimum Inhibitory Concentration (MIC) was determined by contrasting the absorbance value before and after incubation. Minimum Bactericidal Concentration (MBC) was obtained by testing the concentration with negative absorbance value on MSA media incubated for 24 hours. Results: The results of this study indicated that the concentration of 40%, 50%, 60%, 70%, 80%, 90%, and 100% could inhibit the growth of Staphylococcus aureus but these concentrations had yet been able to kill Staphylococcus aureus. Conclusion: The MIC of mauli banana and basil leaves extract combination against S aureus presentts at 40% concentration yet MBC cannot be obtained.Keywords : Antibacterial activity, Basil leaf, Dilution method, Mauli banana stem, Staphylococcus aureus